Behind the Empty Plate: : A Phenomenological Exploration of Psychosocial Factors in Binge Eating Behavior Among University Students - Adek Titik Chumaerah; Istiana Tajuddin; A. Juwita Amal (International Journal of Educational Administration, Management, and Leadership, 2025)
Binge eating behavior, characterized by loss of control during eating episodes, is increasing in prevalence among university students and can lead to serious physical and psychological consequences. According to the National Comorbidity Survey-Replication, approximately 1 in 25 individuals experience binge eating at some point in their lives, with higher rates in women (1 in 20) compared to men (1 in 25). This research aims to explore the psychosocial factors that contribute to binge eating behavior in university students in Indonesia, particularly in the context of changing patterns during the COVID-19 pandemic. Using a qualitative phenomenological approach with interpretative phenomenological analysis, we interviewed three female students (aged 21-23 years) who exhibited binge eating behavior based on the Binge Eating Scale (BES). Interviews were conducted both face-to-face and online between August and November 2022, with each session lasting 90-180 minutes. Five main psychosocial factors emerged: emotional eating (including stress, emotional stabilization, boredom, and sadness), social and cultural influences (including family eating habits and cultural beliefs about food waste), thoughts about food, external eating (including sensory pleasure and food availability), and the use of food as a stimulator (including diet retaliation, sleep induction, and weight gain efforts). These findings highlight the complex interaction between psychological and social factors in the development and maintenance of binge eating behavior. Understanding these factors can inform effective prevention and intervention strategies to address problematic eating behaviors among university students and potentially prevent the development of clinical eating disorders and related physical and psychological consequences.